Studi Kawasan Permukiman Berbasis Kesesuaian Lahan di Kecamatan Belopa Kabupaten Luwu: Permukiman di Kecamatan Belopa Kabupaten Luwu - Angga Amartha Auliah; Rudi Latief; Emil Salim Rasyidi (Fakultas Teknik Universitas Bosowa, 2022)
This study aims to determine the need for residential land in Belopa Regency, Luwu Regency, where Belopa District is the center of local activities so that it triggers a fairly rapid population growth every year. Then this study also aims to determine the direction of development of residential areas in Belopa District, Luwu Regency. The method used in this research is hierarchical process analysis (AHP), assessment analysis, spatial analysis, qualitative descriptive and quantitative descriptive. The results of this study are the level of land demand in Belopa Regency, Luwu Regency and the direction of regional development that is quite adequate in Belopa Regency, Luwu Regency until 2040. This study shows that the classification of residential land in Belopa District, Luwu Regency is divided into 3 classes, namely appropriate, appropriate and not appropriate. . for land use needs in 2040 can be accommodated in the appropriate land classification.